Urban Modeling Interface (UMI): Analisis Keberlanjutan Kawasan Balimester di Jatinegara Jakarta Timur - ., Hakim; Endangsih, Tri; Iskandaria, Harfa (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 9 No 2 (2022): October 2022, 2022)
Over the past few decades, cities have experienced severe social and economic pressures, which disproportionately impact the urban environment. As a result, the environment has decreased in quality, which is characterized by increasing CO2 emissions and energy operating costs. Sustainable city development is considered as a step toward developing a sustainable environment for the community. Therefore, this research orients its discussions toward the regeneration of urban settlements to improve the quality of their urban environments. Taking Balimester as its case study, it aims at generating a model that develops a sustainable settlement in a densely populated area. It uses simulation as its method and is aided by an Urban Modelling Interface as its tool that comes with three parameters. This modeling shows that a Floor Area Ratio (FAR) of 0.43 with a total area of ± 427,233 m². This FAR produces an operational energy of 3983 kwh/m2/year and an embodied energy of 216 kwh/m2/ year. This figure is classified as very high relative to the standard figure of 240 kWh/m2/year. The mobility level in the context of walkability is 21-68, and a reading of 21-69 for the level of bikeability. These indicate that the residential area in Balimester is unsustainable. Keywords: hybrid settlements; regeneration; Urban Modeling Interface (UMI); sustainable development   Abstrak Selama beberapa dekade terakhir, kota-kota telah mengalami tekanan sosial dan ekonomi yang parah, yang memiliki dampak yang tidak proporsional terhadap lingkungan perkotaan. Akibatnya, lingkungan mengalami penurunan kualitas yang ditandai dengan meningkatnya emisi CO2 dan biaya operasional energi. Pembangunan kota yang berkelanjutan dianggap sebagai langkah untuk menciptakan lingkungan berkelanjutan bagi masyarakat. Oleh karena itu, penelitian ini penting dilakukan untuk meremajakan permukiman dalam meningkatkan kualitas lingkungan perkotaan. Dengan mengambil Kawasan Balimester sebagai studi kasusnya, penelitian ini bertujuan untuk menemukan model pengembangan permukiman berkelanjutan di daerah padat penduduk. Metode penelitian dengan metode simulasi menggunakan perangkat Urban Modeling Interface dengan tiga parameter. Hasil pemodelan diperoleh nilai Floor Area Ratio (FAR) sebesar 0,43 dengan total luas lahan ± 427.233 m². Nilai FAR menghasilkan nilai energi operasional sebesar 3983kwh/m2/tahun dan nilai energi perwujudan sebesar 216 kwh/m2/tahun. Nilai ini sangat tinggi dari 240 kwh/m2/tahun sebagai standar penggunaan energi. Nilai mobility pada aspek walkability adalah 21-68, dan 21-69 untuk nilai bikeability . Hasil simulasi ini menunjukkan bahwa kawasan permukiman di Balimester tidak berkelanjutan.   Kata kunci: permukiman hibrid; regenerasi; Urban Modeling Interface (UMI); pembangunan   berkelanjutan